Pengaruh Pendapatan, Jumlah Penduduk dan Luas Wilayah Terhadap Pengeluaran Pemerintah Daerah di Sumatera Barat - Delta Susanti; Melti Roza Adry; Mike Triani (Universitas Negeri Padang, 2019)
This research purpose to analysis the effect of (1) income, (2) the population, (3) the area of expenditure of local government in West Sumatra. This type of research includes descriptive and inductive. This study uses BPS data 2010-2016 with data analysis method using panel regression (Pooled Analysis) and classical assumption test with stages (1) Multicollinearity test, (2) Heteroscedasticitytest. The results of this study indicate that negative income has a significant effect on government spending. Negative population is not significant to local government spending. And then, the last variable the size of the area has a significant negative effect on the expenditure of the local government in accordance with the research of Nazara and Nurkholis.